Optimization of robotic path planning and navigation point configuration based on convolutional neural networks - Wu, Jian; Li, Huan; Li, Bangjie; Zheng, Xiaolong; Zhang, Daqiao (Frontiers in Neurorobotics, 2024)
This study introduces a novel approach for enhancing robotic path planning and navigation by optimizing point configuration through convolutional neural networks (CNNs). Faced with the challenge of precise area coverage and the inefficiency of traditional traversal and intelligent algorithms (e.g., genetic algorithms, particle swarm optimization) in point layout, we propose a CNN-based optimization model. This model not only tackles the issues of speed and accuracy in point configuration with Gaussian distribution characteristics but also significantly improves the robot's capability to efficiently navigate and cover designated areas with high precision. Our methodology begins with defining a coverage index, followed by an optimization model that integrates polygon image features with the variability of Gaussian distribution. The proposed CNN model is trained with datasets generated from systematic point configurations, which then predicts optimal layouts for enhanced navigation. Our method achieves an experimental result error of less than 8% on the test dataset. The results validate the proposed model's effectiveness in achieving efficient and accurate path planning for robotic systems.